PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KINERJA ORGANISASI PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Monalisa Rahmatika Arman; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The Organizational commitment have an important role in order to maximize theperformance, due to the low performance of the company ' s directly attributable to theemployees are often not in line with the expected by the company. This of course will be aproblem if the company performance great good for the worse by the absence oforganizational employees commitment against the company.This study aims to analyze the effect of organizational commitment and employeeperformance to performace company’s. There are 129 respondents for the samplesemployees of PT. Bank Riau Kepri Pekanbaru Main Branch.From the results of this study proved that the positive effect on organizationalcommitment to performace company’s, which means that the higher the level oforganizational commitment performace company’s,is increasing. To increase the performacecompany’s, the implications that can be carried out by PT. Bank Riau Kepri Pekanbaru MainBranch is to increase employee organizational commitment.Keywords: Organizational Commitmen, employee Performance and PerformanceOrganization.